THE EFFECT OF USING VIDEO ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT AT SMA N 2 PEMATANGSIANTAR - Rawiyah Damanik and Bachtiar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study is an attempt to discover the effect of using video on students’achievement in writing descriptive text. It was conducted by using experimentalresearch design. The Population of this research was the tenth (X) grade studentsof SMAN 2 Pematangsiantar which consists of eleven parallel classes with thetotal number of students is 389. The samples of this research were taken byrandom sampling through lottery technique. The result was class X PMIA 2consisted of 30 students became the experimental group and class X PMIA 7consisted of 30 students became the control group. The experimental group wastaught by using Video while the control group was taught without using Video.The instrument for collecting the data was writing test. The data were analyzed byusing t-test formula. The result shows that the value of t-observed (5.078) ishigher than the value of t-table (2.000) (α = 0.05) with the degree of freedom (df)= 58. It means that there is a significant effect of using Video on students’achievement in writing descriptive text. So, the alternative hypothesis (Ha) isaccepted.